Pendampingan Untuk Meningkatkan Kualitas Baca Tulis Al-Qur’an (B.T.Q) Di T.Pq Nurul Hidayah Mulyo Rejo Kampung Baru Kepung Kediri - Fitriya Janies Erta Yuswanti (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Education as a vital thing for life, because it is a process of social interaction either teaching or training with the aim of improving the quality of self-ability to prepare students to face the era of globalization. BTQ is a learning activity that is always taught from elementary school to university level. This shows how important it is to learn to read and write the Al-Quran because it is the basic ability that supports all Islamic subjects. The research approach used in this study is the PAR method or Participatory Action Research. Participatory Action Research is a research model that is looking for something to link the research process to the process of social change. The emergence of this activity based on the results of observations and research from the author sees that material about reading and writing the Qur'an is still limited to introduction and has not been conveyed in depth in the family environment, as well as during Religion lessons in school classes it is still limited to introduction, this is due to limited time. given by the school.